UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR FIQIH MELALUI SCIENTIFIC LEARNING DI MAN 1 CILEGON - Turiyah Turiyah (Universitas Muhammadiyah Metro, 2019)
Success in the subject of fiqh is one component that measures the success of the learning process, in addition to achieving academic achievement but has a major influence on the growth and development of student character. So by motivating students is one form of encouragement that comes from outside the individual or from within the individual to influence every activity of students in participating in learning activities. Based on the phenomena that arises there are still many students who follow the lessons have not been effective so that the value obtained is still under standard. This needs an innovation in the form of a learning approach so that classroom learning is not monotonous.Keywords. Effort, motivation, results